Clinical outcome of biodegradable polymer sirolimus-eluting stent and durable polymer everolimus-eluting stent in patients with diabetes - Ryota Kakizaki; Yoshiyasu Minami; Masahiro Katamine; Aritomo Katsura; Yusuke Muramatsu; Takuya Hashimoto; Kentaro Meguro; Takao Shimohama; Junya Ako (Cardiovascular Diabetology, 2020)
Abstract Background Diabetes mellitus is a risk for increased incidence of adverse clinical events after percutaneous coronary intervention. However, the difference in the incidence of adverse clinical events according to stent type in patients with diabetes remains to be elucidated. In the present study, we aimed to compare the clinical outcomes between patients treated with the biodegradable polymer sirolimus-eluting stents (BP-SES) and the durable polymer everolimus-eluting stents (DP-EES) among patients with diabetes. Methods Among 631 lesions in 510 consecutive patients treated with either BP-SES or DP-EES, 165 lesions in 141 patients with diabetes mellitus and stable angina pectoris were identified and classified into the BP-SES group (48 lesions in 44 patients) and the DP-EES group (117 lesions in 100 patients). The incidence of adverse clinical events after stent implantation was compared between the 2 groups. Results There was no significant difference in the prevalence of conventional risk factors, lesion characteristics, and procedural characteristics between the 2 groups. During median 386 [334–472] days follow-up, the incidence of target lesion revascularization (11.4 vs. 2.0%, p = 0.003) and device-oriented clinical endpoint (13.6 vs. 6.0%, p = 0.035) in the BP-SES group was significantly greater than that in the DP-EES group. A univariate model demonstrated that the BP-SES usage was significantly associated with the higher incidence of target lesion revascularization (odds ratio, 6.686; 95% confidence interval, 1.234–36.217; p = 0.028). Conclusion BP-SES was associated with the greater incidence of TLR than the DP-EES in patients with diabetes mellitus. Further studies with larger cohorts and longer follow-up are required to confirm the present results.